Baryons shaping dark matter haloes. Issue 4 (29th December 2020) - Cataldi, P; Pedrosa, S E; Tissera, P B; Artale, M C
ABSTRACT: In this work, we aim at investigating the effects of baryons on the dark matter (DM) haloes structure, focusing on the correlation between the presence and importance of stellar discs and the halo shapes. We study the properties of a subsample of DM haloes from Fenix and eagle cosmological simulations. We inspect the central regions of haloes in the mass range [10.9-992.3] × 10^10 M_ at z = 0, comparing the hydrodynamic runs and their dark matter only (DMo) counterparts. Our results indicate that baryons have a significant impact on the shape of the inner halo, mainly within ∼20 per cent of the virial radius. We find haloes to be more spherical when hosting baryons. While the impact of baryons depends on the mass of the haloes, we also find a trend with morphology which suggests that the way baryons are assembled is also relevant in agreement with previous works. Our findings also indicate that disc galaxies preferentially form in haloes whose DMo counterparts were originally more spherical and with stronger velocity anisotropy. The presence of baryons alter the orbital structure of the DM particles of the haloes, which show a decrease in their velocity anisotropy, towards more tangentially biased orbits. This relative decrease is weaker in the case of disc-dominated galaxies. Our results point out to a cosmological connection between the final morphology of galaxies and the intrinsic properties of their DM haloes, which gets reinforce by the growth of the discs.